Altered mitochondrial function: a clue therapeutic strategies between metabolic dysfunction-associated steatotic liver disease and chronic kidney disease? - Bai, Jiang; Zhang, Lijuan; He, Letian; Zhou, Yun (Frontiers in Nutrition, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) and chronic kidney disease (CKD) have been demonstrated to be intricately linked in a multitude of research studies. The reclassification of MASLD has prompted a reevaluation of its epidemiological patterns and the associated risk of CKD. This is crucial as MASLD, focusing on cardiometabolic factors, might have a more pronounced association with CKD than NAFLD. Additionally, mitochondrial dysfunction has been implicated in the pathogenesis of both MASLD and CKD. Studies on metabolic dysfunction-associated steatohepatitis mouse models have revealed significant mitochondrial alterations, such as loss of cristae and impaired function in the kidneys, underscoring the critical importance of mitochondrial integrity in these pathologies. This review offers an extensive overview of the existing literature, covering the following key aspects: (a) presenting the latest epidemiological findings that elucidate the relationship between MASLD and CKD; (b) kidney pathological changes associated with MASLD; (c) mitochondrial alterations in MASLD and CKD, including oxidative stress, dynamics, and mitophagy; and (d) potential mitochondrial-targeted therapies.